Question
upstudy study bank question image url

\( \begin{array}{l} \text { Find the derivative of the function. }\\ y=\frac{7 x}{\sqrt{x^{2}+4}} \end{array} \)

Ask by Weaver Matthews. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( y = \frac{7x}{\sqrt{x^{2}+4}} \) is \( y' = \frac{28}{(x^{2}+4)^{3/2}} \).

Solution

We want to find the derivative of   y = (7x) / √(x² + 4). Step 1. Write the function in quotient form:   Let u = 7x  and v = √(x² + 4) = (x² + 4)^(1/2). Step 2. Find u′ and v′.   u′ = 7.   For v, use the chain rule:    v = (x² + 4)^(1/2) so    v′ = (1/2)(x² + 4)^(−1/2) · (2x) = x / √(x² + 4). Step 3. Apply the quotient rule:   y′ = (v·u′ − u·v′) / v². Plug in the values:   y′ = [√(x² + 4) · 7 − 7x · (x/√(x² + 4))] / (x² + 4). Step 4. Simplify the expression:   The numerator becomes:    7√(x² + 4) − 7x²/√(x² + 4) = 7/√(x² + 4) · [ (x² + 4) − x² ] = 7/√(x² + 4) · 4 = 28/√(x² + 4). So now:   y′ = (28/√(x² + 4)) / (x² + 4). Step 5. Write in exponent form:   Note that √(x² + 4) = (x² + 4)^(1/2), so:   y′ = 28 / [ (x² + 4)^(1/2) · (x² + 4) ] = 28 / (x² + 4)^(3/2). Final Answer:   y′ = 28 / (x² + 4)^(3/2).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of the function \( y=\frac{7 x}{\sqrt{x^{2}+4}} \), we will use the quotient rule. The quotient rule states that if you have a function \( y = \frac{u}{v} \), then \( y' = \frac{u'v - uv'}{v^2} \). Here, let \( u = 7x \) and \( v = \sqrt{x^2 + 4} \). Calculating the derivatives: - \( u' = 7 \) - To find \( v' \), we apply the chain rule: \[ v = (x^2 + 4)^{1/2} \Rightarrow v' = \frac{1}{2}(x^2 + 4)^{-1/2}(2x) = \frac{x}{\sqrt{x^2 + 4}} \] Now substituting back into the quotient rule: \[ y' = \frac{(7)(\sqrt{x^2 + 4}) - (7x)\left(\frac{x}{\sqrt{x^2 + 4}}\right)}{(x^2 + 4)} \] Simplifying this gives: \[ y' = \frac{7\sqrt{x^2 + 4} - \frac{7x^2}{\sqrt{x^2 + 4}}}{x^2 + 4} \] Combining terms in the numerator leads to: \[ y' = \frac{7(x^2 + 4) - 7x^2}{(x^2 + 4)\sqrt{x^2 + 4}} = \frac{28}{(x^2 + 4)\sqrt{x^2 + 4}} \] So the derivative is: \[ y' = \frac{28}{(x^2 + 4)\sqrt{x^2 + 4}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy